Conjugation of micro/nanocurcumin particles to ZnO nanoparticles changes the surface charge and hydrodynamic size thereby enhancing its antibacterial activity against Escherichia coli and Staphylococcus aureus. (28th June 2020) - Shome, Soumitra; Talukdar, Anupam Das; Tewari, Sujit; Choudhury, Sudip; Bhattacharya, Mrinal Kanti; Upadhyaya, Hrishikesh
Abstract: Nanobiotechnology‐mediated synthesis of ZnO nanoparticles, micro/nanocurcumin, and curcumin–ZnO nanocomposites and their characterization followed by comparative study of their antibacterial, antioxidant, and iron‐chelating efficiency at various dosages are discussed. Micro/nanocurcumin and ZnO nanoparticles were synthesized using curcumin and zinc nitrate as precursor and then conjugated by sonication to synthesize curcumin–ZnO nanocomposites. The synthesized nanoparticles were then characterized by using ultraviolet‐visible spectroscopy, X‐ray diffraction, Scanning electron microscopy, Fourier‐transform infrared spectroscopy, and dynamic light scattering analysis. After that, the antibacterial activity of the synthesized nanoparticles was evaluated by the optical density (OD600 ) method against Escherichia coli and Staphylococcus aureus cells. The DPPH (2, 2‐diphenyl‐1‐picrylhydrazyl ), hydroxyl radical scavenging activity, and ferrous ion–chelating efficiency of synthesized nanoparticles were evaluated by spectrophotometry analysis. Nanocurcumin (mean zeta potential = −25 mV; average hydrodynamic diameter = 410 nm) based coating of ZnO nanoparticles (mean zeta potential = −15.9 mV; average hydrodynamic diameter = 274 nm) to synthesize curcumin–ZnO nanocomposites (mean zeta potential = −18.8 mV; average hydrodynamic diameter = 224 nm) exhibited enhanced zeta potential, which resulted in reduced agglomeration, smaller hydrodynamic size in water, improved aqueous solubility, and dispersion. All the aforesaid factors including the synergistic antibacterial effect of ZnO nanoparticle and micro/nanocurcumin contributed to increased antibacterial efficiency of curcumin–ZnO nanocomposites. Micro/nanocurcumin due to its better water solubility and small hydrodynamic diameter exhibited enhanced antioxidant and ferrous ion–chelating efficiency than curcumin. Abstract : Nanobiotechnology mediated synthesis of curcumin‐ZnO nanocomposites with reduced size and improved bioactivity